Aryl hydrocarbon receptor facilitates HSV-1 lytic infection by enhancing viral gene transcription and receptor expression - Pu Huang; Pu Huang; Xiaohong Pan; Hongli Chen; Hongli Chen; Mengyue Lei; Ying Ma; Xiaomei Guo; Xiaomei Guo; Jiaxin Xie; Jixiong Li; Jixiong Li; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Herpes simplex virus type 1 (HSV-1) is a major human pathogen with significant morbidity in neonates and immunocompromised individuals. However, antiviral drugs targeting HSV-1 are emerging with antiviral resistance, highlighting the need to identify new targets for future treatment. Once HSV-1 enters the host cells, it recruits host factors to facilitate viral life cycle. In this study, we showed that aryl hydrocarbon receptor (AhR), a ligand-activated nuclear receptor, is required for HSV-1 effective replication and offers an opportunity for pharmacological intervention. Our results showed that HSV-1 infection activates AhR signaling in an interferon-dependent manner. Pharmacological inhibition or knockout of AhR reduced the expression of viral proteins and infectious progeny, while increased AhR signaling promoted the expression of viral proteins and viral replication. Mechanistically, AhR formed a transcription complex with cyclin T1, VP16 and RNA Pol II in the nucleus, bound to viral gene promoters, and promoted their transcription. Additionally, AhR promoted viral replication partially by facilitating the expression of multiple viral receptors. Collectively, AhR is a proviral host factor for HSV-1, and thus may be used as a promising host-directed antiviral target.